Interventions to identify and manage depression delivered by 'nontraditional' providers to community‐dwelling older adults: A realist review - Tom Kingstone; Carolyn A. Chew‐Graham; Nadia Corp (Wiley, 2022)
Abstract Background Mental health problems experienced by older adults (60+ years of age) may remain hidden due to individual and system‐level barriers. Opportunities to support early identification and management are therefore crucial. The National Health Service recommends wider public services that are embedded within local communities, but are not traditionally part of the healthcare landscape (i.e., 'nontraditional'), could facilitate engagement with healthcare by members of the public. Evidence for interventions involving Fire and Rescue, Police, Library services and postal workers, as nontraditional providers of mental health services, has not been synthesized previously. This review aims to understand how, why and in what contexts mental health interventions delivered by these nontraditional providers, to older adults, work. Methods A realist review of interventions to identify and/or manage mental health problems (depression with or without anxiety) experienced by older adults. Systematic, cluster and iterative literature searches were conducted. Intervention evidence was appraised for rigour and explanatory relevance and then coded to inform context‐mechanism‐outcome configurations (CMOCs). A public advisory group supported our initial evidence search strategy and definition of key terms. This review is registered with PROSPERO (CRD42020212498). Results Systematic searches revealed a dearth of evidence reporting mental health interventions delivered by nontraditional providers. Our scope was adjusted to consider interventions delivered by Fire and Police services only and for wider health and wellbeing concerns (e.g., dementia, falls prevention, mental health crises). Forty‐three pieces of evidence were synthesized. Key themes included: legitimizing expanded roles, focusing on risk, intervention flexibility and organization integration; further subthemes are described. Themes map onto CMOCs and inform a preliminary programme theory. Findings were transposed to mental health contexts. Conclusions Findings highlight challenges and opportunities for Fire and Police services, as nontraditional providers, to deliver interventions that identify and/or manage mental health problems among older adults. Our programme theory explains what could work, how, for whom and also by whom (i.e., which public services). Further empirical evidence is needed to test interventions, understand acceptability and inform implementation. Patient or Public Contribution A public advisory group comprising older adults with lived experience of mental health problems and informal caregivers contributed to the original application, reviewed the scope and informed the approach to dissemination.